Analysis of research trends (2014-2023) on oxidative stress and male fertility based on bibliometrics and knowledge graphs - Du, Chao; Yu, Yuexin; Fan, Xinyue (Frontiers in Endocrinology, 2024)
Background: Oxidative stress (OS) is considered one of the major factors affecting male fertility, and research in this field has seen constant growth year by year. Currently, around 700 relevant papers are published each year, with a trend of further growth. Therefore, this study systematically summarizes the literature published in the last decade from a bibliometric perspective, revealing the dynamic development of the field, identifying research hotspots, analyzing future trends, and providing reference for further research. Methods: Relevant literature on oxidative stress and male fertility was retrieved from the Web of Science Core Collection (WoSCC) database, covering the timespan from 2014 to 2023 and including two types, articles and reviews. CiteSpace and VOSviewer were used for bibliometric analysis, including cluster analysis, co-occurrence analysis, co-citation analysis, and burst analysis of countries/regions, institutions, journals, authors, references, and keywords. Results: This paper studied a total of 5,301 papers involving 107 countries/regions, with China having the highest number of publications (898 papers) and the United States having the highest centrality (0.62). Burst analysis of journal citations revealed the emergence of many new journals (e.g., Antioxidants-Basel, Front Endocrinol) after 2021, indicating continuous expansion and development in this field. Cluster analysis of co-cited references and co-occurring keywords divided the research into areas such as oxidative stress and male infertility, oxidative stress level detection, and antioxidants. The keywords associated with research hotspots shifted from oxidative stress detection, sperm DNA damage, apoptosis, and redox potential to DNA methylation, embryonic development, infection, polyunsaturated fatty acids, and antioxidants. Conclusion: Bibliometric methods provide an intuitive reflection of the development process in the field of oxidative stress and male fertility, as well as the analysis of research hotspots in different periods. Research on oxidative stress and embryonic development, as well as antioxidant health management, may become hotspots in future research.